Does E-Worksheet Based on Tri-N Principles Give Support to Improve Students' Ability to Think Critically and Creatively? - Latifah, Dyah Ayu Retno Budi; Widodo, Sri Adi; Istiqomah, Istiqomah; Perbowo, Krisna Satrio (Jurnal Pendidikan Matematika, 2024)
The rationale of this study was students' critical and creative thinking skills in learning mathematics are still low. Many strategies to improve those abilities, one of the strategies is using e-worksheets. This research aims to explore the effect of e-worksheets based on Tri-N Principles give support to improve the creative and critical thinking ability of students in learning mathematics. Tri-N was chosen since one of Ki Hajar Dewantara's principles, including Niteni, Nirokke, and Nambahi. These principles have provided support to improve the creative and critical thinking ability of students in learning. An experimental method with a posttest-only design type was used in this research. The random cluster was used to take a research sample of 52 students from the Junior High School of Pembangunan Piyungan in two classes. The instrument used is a mathematical test in the form of a description which aims to measure students' mathematical critical and creative thinking abilities. The hypothesis test uses multivariate analysis because this study has two dependent variables. The results revealed that the calculated F is  with a significance coefficient of .000. For this reason, it can be concluded that e-worksheets based on Tri-N principles improve critical and creative thinking skills. So, e-worksheets based on Tri-N principles can be used as an alternative to improve the creative and critical thinking ability of students in learning mathematics. Penelitian ini dilatarbelakangi oleh kemampuan berpikir kritis dan kreatif matematis siswa masih belum optimal. Banyak cara yang dapat dilakukan untuk meningkatkan dua kemampuan tersebut, diantaranya menggunakan e-worksheet pada pembelajaran matematika. Tujuan dari penelitian ini untuk mengetahui pengaruh e-worksheet berbasis Tri N terhadap kemampuan berpikir kritis dan kreatif siswa pada pembelajaran matematika. Dipilihnya Tri-N karena salah satu ajaran Ki Hajar Dewantara ini yang dapat menuntun siswa untuk memiliki kemampuan berpikir kritis, kreatif, inovatif dan pemahaman konsep melalui kegiatan Niteni, Nirokke, Nambahi. Metode eksperimen dengan tipe posttest only design digunakan pada penelitian ini. Random cluster digunakan untuk mengambil sampel penelitian dengan ukuran 52 siswa SMP Pembangunan Piyungan yang tergabung dalam dua kelas. Instrumen yang digunakan adalah tes matematika berbentuk uraian yang bertujuan untuk mengukur kemampuan berpikir kritis dan kreatif matematis siswa. Uji hipotesis menggunakan analisis multivariat karena penelitian ini memiliki dua variabel terikat. Hasil penelitian menunjukkan bahwa F hitung sebesar  dengan koefisien signifikansi sebesar . Untuk itu dapat disimpulkan bahwa e-worksheet berbasis Tri-N meningkatkan kemampuan berpikir kritis dan berpikir kreatif daripada bahan ajar e-worksheet biasa. Berkaitan dengan ini bahan ajar e-worksheet berbasis Tri-N dapat digunakan sebagai alternatif dalam pembelajaran matematika untuk meningkatkan kemampuan berpikir kritis dan kreatif matematis siswa SMP.